Boys Don't Wear Nailpolish - Chauhan, Siddharth (India, 2013)
A mother's battle against gender stereotyping to protect her child's individuality in a society that promotes images of masculinity but how far will she go to defeat the established order of things?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films